Phonology Decoded: An Exploration into the Intricacies of Language Sound Systems - Miftahul Jannah; Fahima Mashalani; Yani Lubis; Jennifer Cabrelli Amaro (Tinta Emas Institute, 2023)
The research explores the phonological inventory of different languages, investigating the phonemes, allophones, and distinctive features that shape their unique sound patterns. Furthermore, the paper delves into phonological processes, such as assimilation, dissimilation, and vowel harmony, which govern sound changes within a language. It investigated phonotactics, the study of permissible sound combinations and constraints, shedding light on syllable structures, onset and coda clusters, and phonological constraints that shape the phonotactic patterns in different languages. Additionally, the research explores the role of phonology in language acquisition, examining how children acquire the phonological rules and patterns of their native language. It also delves into the role of phonology in language variation and change, investigating how phonological shifts occur over time and contribute to dialectal and historical linguistic differences.Overall, this paper provides a comprehensive overview of phonology, highlighting its importance in understanding the intricacies of sound systems in language. By examining the foundational principles and patterns of phonology, this research aims to deepen our understanding of how sounds function and contribute to the rich tapestry of human communication.